Watching over you [large type] - Foster, Lori, 1958- (Foster, Lori, 1958- McKenzies of Ridge Trail, 2023)
"While investigating a criminal network, Detective Crosby Albertson keeps crossing paths with members of the highly trained, suspiciously well-informed McKenzie family. They're always one step ahead of him -- especially their alarmingly attractive intel specialist, Madison. And Crosby needs to find out why. Madison McKenzie is the tech and surveillance whiz of her family's operation. When a recent case introduced her to Detective Albertson, she found herself irresistibly drawn to the sexy and mysterious cop. There's just one problem. He's a detective and her family's work is secret. When Crosby starts digging for information about the McKenzies, Madison's got to get him off the scent . . . while keeping him at a safe distance."--